Hilda Agnes Hübner Flores: memórias de uma intelectual educadora - Brandenburg, Cristine (2019)
This Thesis deals with a theme that articulates the knowledge about the immigration of bohemians, the engagement of intellectual women in the construction of literary research movements on women and the history of education in Rio Grande do Sul - RS works, more specifically, with Hilda's biography Agnes Hübner Flores pondering her research as a historian. The biographical academic work aimed to answer the following problem: What educational background was experienced by Hilda Agnes Hübner Flores to enable a rural woman, born in southern Brazil in 1930, to become an intellectual historian about Bohemian immigrants and engaged in women's movements? The aim was to biograph Hilda Flores, with an emphasis on educational background, her school career and intellectual performance. In other words, the biographical narrative of a German descendant born in Linha Duvidosa, in the interior of the municipality of Venâncio Aires - Rio Grande do Sul, in the 1930s, who went through different schooling becoming a teacher, a historian engaged in the movement of women, who she acted actively in society, discussing German immigration in Brazil and the place offered to women in society. The relevance of the biography was to elaborate a historical record about Hilda Flores, an intellectual who contributed to the understanding of German immigration in Rio Grande do Sul and to the history of the education of women, being one of the forerunners of the Words collection of the Literary Academy Fermina de Letras e of Bohemian immigration studies. The registration of the biographer allows to broaden the understanding about female education in the 18th and 19th centuries in southern Brazil, as well as about the migratory context of Germans who moved to Brazil and influenced the country's socio-cultural constitution. The scope was contemplated through a research supported theoretically in the assumptions of cultural history (CERTEAU, 2018) and methodologically in oral and biographical history (ALBERTI, 2013; 2015; FERREIRA, AMADO, 2016; DOSSE, 2015; VILAS-BOAS, 2014) intertwined with other documentary contributions, such as books, photographs, personal and school documents, awards, course brochures, among others (MEIHY, RIBEIRO, 2011). This study proved that Hilda Agnes Hübner Flores is the first researcher on Bohemians in Rio Grande do Sul and one of the first in the country with more ownership of the subject to date. The findings prove that the biographer is embedded in the feminism period of the 70s and 80s as an intellectual woman and participant in feminist movements.